Mapping the Literature on Digital Humanities: A Bibliometric Study Using Scopus Data - Basak, Moutusi; Roy, Sanku Bilas (DESIDOC Journal of Library & Information Technology, 2023)
Digital humanities (DH) has become a hot topic among both humanities scholars and library and information services (LIS) professionals. To conduct this research, researchers searched Scopus database for articles published between 2006 and 2020, as of March 2021 which brought out a set of 2643 publications. MS-Excel, R-programming language and VosViewer were used to analysis the collected data. The significant increase of publications in DH over last six years (2015-2020) is observed. The annual percentage of growth rate is 34.91. It is found that the average authors per document are 1.8 and the collaborative index is 2.53 in this study. USA, UK and Germany emerged as the major research contributor. In the co-occurrence network of keywords, the value of clustering coefficient is 0.072. This study gives a better knowledge of collaborative processes in the digital humanities. The findings of this study will raise the profile of DH among researchers who are unfamiliar with it in anticipating future.